Phenotypic and genetic parameters of milk yield traits in first-calf heifers of Holstein-Friesian breed - Mladen Popovac; Aleksandar Miletić; Nikola Raguž; Radmila Beskorovajni; Dragan Stanojević; Mihailo Radivojević; Nenad Mićić; Nenad Đurić (Mljekarstvo, 2020)

(untitled)
The objective of this paper was to study variability, heritability and correlation of the three production traits in 1409 first-calf heifers of Holstein-Friesian breed; including the determination of the quantity of milk during lactation (ML), the quantity of milk fat during lactation (MM) and the quantity of protein during lactation (PR). According to the obtained results it could be concluded that there were statistically significant differences (P<0.01, P<0.05, P<0.001) between ML, MM and PR regarding the effect of season of the first calving and the length of the first lactation. In addition, there were also significant differences (P<0.01, P<0.001) between ML and PR with respect to the effect of farm on which animals were raised, while on MM variability the year and age at first calving had a significant effect (P<0.05). A share of Holstein genes and the ration which animals were fed had no effect (P>0.05) on variability of any of the examined traits, while the farm on which animals were raised had no effect (P>0.05) on MM, and year and age at first calving did not demonstrate (P>0.05) statistically significant effect on ML and PR. By applying the animal model, based on the use of kinship matrix which involved 3867 animals, by help of REML methodology following heritability coefficients were evaluated: ML h2= 0.25; MM h2= 0.40; PR h2= 0.37. Coefficients determined for genetic and phenotypic correlations indicated existence of complete and positive correlations between these traits the interval of values being from rg = 0.96 between ML and MM to rg = 1.00 between ML and PR.